Hyperactive behaviour in Angelman syndrome: the association with sleep problems and age of epilepsy onset. Issue 7 (5th May 2021) - Bakke, K. A.; Howlin, P.; Helverschou, S. B.
Abstract: Background: Sleep problems are common in many neurodevelopmental disorders, but little is known about how sleep is related to behavioural symptoms in Angelman syndrome (AS) or other genetic disorders. Hyperactive behaviour, sleep problems and epilepsy seem to be more common in AS than in other genetic conditions associated with severe intellectual disability. We hypothesised that both more sleep problems and earlier onset of epileptic seizures would predict more symptoms of hyperactivity. Hence, the aim of the project was to explore the association between hyperactive behaviour, sleep problems and age of epilepsy onset in individuals with AS. Method: All known parents/guardians ( n  = 115) of individuals with AS in Norway were invited to participate in this descriptive correlational study. Fifty‐six individuals (49%) responded, and 42 people (25 male and 17 female; mean age 18.5 years, range 2–57 years) with genetically verified AS were included. Scores for 'hyperactivity' and 'sleep problems' were derived from questionnaire data. Information on epilepsy was obtained from medical records. Results: 'Hyperactivity' was positively correlated with 'total sleep problems' ( r  = 0.46, P  = 0.002) and negatively correlated with 'age of epilepsy onset' ( r  = −0.47, P  = 0.01). 'Age of epilepsy onset' was not correlated with 'total sleep problems'. An overall multiple regression model with 'hyperactivity' as the dependent variable and 'age of epilepsy onset' and 'total sleep problems' as covariates was significant ( R 2  = 0.39, F  = 8.16, P  = 0.002). Hence, hyperactivity in AS could be predicted from both age of epilepsy onset and current sleep problems. Conclusions: Sleep problems may increase hyperactivity symptoms in individuals with AS. The association between hyperactivity and sleep problems in AS indicates that both should be investigated together as part of routine clinical assessment and intervention for either area of difficulty. Younger age of epilepsy onset was associated with more hyperactivity in AS, which may be related to encephalopathic effects of seizures and epilepsy.